Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan Manufaktur Di BEI Periode 2015-2017 - Lukman Surjadi; Viviana (Jurnal Ekonomi, 2019)
This study aims to examine the effect of company size, profitability, and business risk on capital structure in listed manufacturing companies in the Indonesian Stock Exchange period 2015-2017. This study uses 24 manufacturing companies as a sample in this study and also use multiple-regression analysis. The results of this study indicate that company size has a significant positive effect on the capital structure while profitability and business risk has a not significant negative effect on capital structure.